2013
DOI: 10.1155/2013/624757
|View full text |Cite
|
Sign up to set email alerts
|

Association between RAS Gene Polymorphisms (ACE I/D, AGT M235T) and Henoch-Schönlein Purpura in a Turkish Population

Abstract: Henoch-Schönlein purpura (HSP) is a small-vessel vasculitis of autoimmune hypersensitivity, and renin-angiotensin system (RAS) regulates vascular homeostasis and inflammation with activation of cytokine release. Thus, we aimed to investigate the association between HSP and ACE I/D and AGT M235T polymorphisms. Genotyping was determined by allele specific PCR and PCR-RFLP. We obtained a significant difference in genotype distribution (p = 0.003) and allele frequencies (p < 0.001) of ACE I/D polymorphism between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Of these, 70 studies were excluded according to the inclusion and exclusion criteria, five articles 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] were included in our meta-analysis ( Figure 1). The retrieved data were recorded as follows: first author's surname, publication year, ethnicity, the number of cases and controls.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 70 studies were excluded according to the inclusion and exclusion criteria, five articles 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] were included in our meta-analysis ( Figure 1). The retrieved data were recorded as follows: first author's surname, publication year, ethnicity, the number of cases and controls.…”
Section: Literature Searchmentioning
confidence: 99%
“…Five studies [9][10][11][12][13] were identified for the analysis of the association between AGT M235T gene polymorphism and the risk of HSP/HSPN (Table 1). They were all conducted in Asians.…”
Section: Characteristics For Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Some current investigations [3][4][5][6] suggested that genetic factors might play a key role in the onset of HSP/HSPN.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the level of ACE leads to vascular inflammation due to cytokine release. 11 Polymorphism of the ACE gene (I/D) and its role in HSP disease has been studied in patients from different populations. 12,13 Considering that HSP disease is a complex disease involving different genetic factors, we planned to evaluate the possible associations of these polymorphisms with the susceptibility to HSP independently and in different joint combinations.…”
mentioning
confidence: 99%